Assessing Executive Abilities Following Acute Stroke with the Trail Making Test and Digit Span - Elaine Tamez; Joel Myerson; Lucy Morris; Desirée A. White; Carolyn Baum; Lisa Tabor Connor (Behavioural Neurology)
The Trail Making Test and Digit Span are neuropsychological tests widely used to assess executive abilities following stroke. The Trails B and Digits Backward conditions of these tests are thought to be more sensitive to executive impairment related to frontal lobe dysfunction than the Trails A and Digits Forward conditions. Trails B and Digits Backward are also thought to be more sensitive to brain damage in general. Data from the Stroke and Lesion Registry maintained by the Washington University Cognitive Rehabilitation Research Group were analyzed to compare the effects of frontal versus nonfrontal strokes and to assess the effects of stroke severity. Results showed that the performance of patients with frontal and nonfrontal strokes was comparable in each condition of both the Trail Making Test and Digit Span, providing no support for the widely held belief that Trails B and Digits Backward are more sensitive to frontal lobe damage. Further, Trails A was as strongly correlated with stroke severity as Trails B, whereas Digits Backward was more strongly correlated with stroke severity than Digits Forward. Overall, the Trail Making Test and Digit Span are sensitive to brain damage but do not differentiate between patients with frontal versus nonfrontal stroke.